Development of a Scale to Measure the Information Efficiency of Agricultural Expert System - Helen, S.; Khaleel, F.M.H. (Indian Journal of Extension Education, 2009)
The world is witnessing a revolution in Information and Communication Technology (lCT) leading to the swift and accurate transfer of message from source to the receiver. The advances in the field of information technology has evolved a number of new modes of communication and the evolution is so rapid that it is becoming difficult to keep pace with acquiring and utilizing the new tool. Local information resource centres are gaining importance with computers carrying expert systems to help farmers to make decisions. It is known that many agricultural research institutes are involved in the development of Agricultural Expert System (AES) to satisfy the information needs of farmers. Here after agricultural expert system is referred as AES as used Lipings (2003). The dissemination of the technologies could be enhanced by using expert systems and other artificial intelligence technologies (Hadi et aI, 2006).